The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.7717/peerj.3050
|View full text |Cite
|
Sign up to set email alerts
|

Real-time monitoring of superoxide anion radical generation in response to wounding: electrochemical study

Abstract: BackgroundThe growth and development of plants is deleteriously affected by various biotic and abiotic stress factors. Wounding in plants is caused by exposure to environmental stress, mechanical stress, and via herbivory. Typically, oxidative burst in response to wounding is associated with the formation of reactive oxygen species, such as the superoxide anion radical (O2•−), hydrogen peroxide (H2O2) and singlet oxygen; however, few experimental studies have provided direct evidence of their detection in plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Equations (28), (33), (37), and (41) are implemented for assessing the responses of the stress-transfer processes hypothesized to contain a single second-order low-pass pathway with fixed kinetic rates but differing in the damping, to a step stress. Equations (45), (49), (53), and (57) are implemented to assess the responses of the stress-transfer processes hypothesized to contain a single second-order band-pass pathway with fixed kinetic rates but differing in damping, to a step stress. The equations to be numericized are implemented according to the following principles: (1) The kinetics is evaluated over a timescale of [0 1] with a temporal resolution of 10 −4 .…”
Section: The Response Corresponding To (˛> ! 0 ) That Is Referred To mentioning
confidence: 99%
“…Equations (28), (33), (37), and (41) are implemented for assessing the responses of the stress-transfer processes hypothesized to contain a single second-order low-pass pathway with fixed kinetic rates but differing in the damping, to a step stress. Equations (45), (49), (53), and (57) are implemented to assess the responses of the stress-transfer processes hypothesized to contain a single second-order band-pass pathway with fixed kinetic rates but differing in damping, to a step stress. The equations to be numericized are implemented according to the following principles: (1) The kinetics is evaluated over a timescale of [0 1] with a temporal resolution of 10 −4 .…”
Section: The Response Corresponding To (˛> ! 0 ) That Is Referred To mentioning
confidence: 99%
“…In photosynthetic organism, generation of reactive oxygen species (ROS) is a quite universal and fast defense mechanism, known to be associated with various stresses both in vivo and in vitro (Yadav and Pospíšil, 2012;Prasad et al, 2015;Prasad et al, 2016;Prasad et al, 2017a;Prasad et al, 2018;Kumar et al, 2019), in both local as well as systemic responses (Grant and Loake, 2000;Slesak et al, 2007). In tomato, it has been observed that hydrogen peroxide (H 2 O 2 ) was produced at the site within an hour of wounding and its level was enhanced even in distant part (upper unwounded leaves) in the following 4 to 6 h (Orozco-Cardenas and Ryan, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In disagreement with our observations, Ruiz‐Pérez et al., (2016) found that EOCL (0.008, 0.08 and 0.8 µg/ml) did not change the ROS content in a genotoxic test using the Salmonella typhimurium TA102 model. Finally, the use of 0.5 and 1 ml EOCL/kg diet was able to enhance hepatic SOD activity, indicating a better capacity to scavenge the anion superoxide, which is a potent inflammatory and oxidant molecule (Prasad et al, 2017). This might suggest that this oil can be an alternative to improve the primary antioxidant defence mechanism system of fish.…”
Section: Discussionmentioning
confidence: 99%